Experimental study and energetic optimization of heat exchange with variable geometry in a parabolic trough collector with a double reflection - REGUE Hanane Maria; Pr. BENCHATTI Ahmed Supervisor Professor U.A.T.Laghouat Dr. BOUALI Belkacem Co-Supervisor Doctor (MCB) U.A.T.Laghouat (Bibliotheque centrale -Unversite de Laghouat, 2020)
This thesis is devoted to the development of a numerical simulation of fluid flow and conjugate heat transfer in a solar thermal parabolic trough collector (PTC) system is presented .The simulation is being carried out on a prototype designed in the Mechanical Laboratory in order to analyze the performance of this system. The main objective is to compare the system performance with and without a secondary reflector (SR).PVSYST software is used to provide numerical temporal values of the solar heat flux in Laghouat city (ALGERIA).Solar flux density values for four days in different seasons have been taken .SolTrace code based on Monte Carlo ray tracing method, is used to determine the heat flux distribution on the absorber tube. The conjugate heat transfer and fluid flow equations in the tube absorber are solved by using ANSYS-CFX CFD software. A comparison between two cases (traditional PTC and PTC with parabolic secondary reflector) with (Therminol VP-1) oil and water as working fluid are analyzed. The obtained results for the first heat transfer fluid(Therminol VP-1) show that the system performance are practically the same for the four seasons. Moreover, the performance of the system with a second reflector is better than that without a second reflector with a ratio of about 1.65. However, for the second heat transfer fluid (water) the simulation results show that the maximum fluid temperatures, useful heat, and system efficiency are reached during the month of June while the minimum values are obtained on the month of December. However, for the months of September and March, the performance of the system is nearly identical. In addition, the performance of the system can be increased by using a secondary reflector with a ratio of about 1.62 to 1.67 .Keywords: Conjugate Heat Transfer, Receiver Tube, Solar Thermal Energy, Solar Parabolic Trough Collector, Secondary Reflector, Ray Tracing, Optical Modeling